Assessing liver stiffness with conventional cut‐off values overestimates liver fibrosis staging in patients who received the Fontan procedure. Issue 5 (6th March 2021) - Cho, Yuki; Kabata, Daijiro; Ehara, Eiji; Yamamoto, Akira; Mizuochi, Tatsuki; Mushiake, Sotaro; Kusano, Hironori; Kuwae, Yuko; Suzuki, Tsugutoshi; Uchida‐Kobayashi, Sawako; Morikawa, Hiroyasu; Amano‐Teranishi, Yuga; et al.
Abstract: Aim: Patients who undergo the Fontan procedure for complex congenital heart disease are prone to liver cirrhosis. Liver stiffness (LS) reflects liver fibrosis stage in patients with chronic viral hepatitis; however, its accuracy in predicting liver fibrosis stage in Fontan patients is controversial. We aimed to clarify the correlation between LS and liver fibrosis stage in Fontan patients. Methods: Fifty‐eight Fontan patients were prospectively measured for LS with transient elastography. We undertook liver biopsy, cardiac catheterization, and laboratory tests in 22 of these patients (median age, 14.7 years; range, 9.9–32.1 years) with LS > 11.0 kPa (median, 19.2 kPa; range, 12.2–39.8 kPa); these elevated LS values suggest liver cirrhosis. Results: Histologically, all patients showed mild‐to‐severe portal and sinusoidal fibrosis but no cirrhosis. Statistically, LS did not predict histological liver fibrosis scores ( p  = 0.175). Liver stiffness was not correlated with central venous pressure ( p  = 0.456) or with the hepatic venous pressure gradient (HVPG; p  = 0.062), although the p value for HVPG was only slightly above the threshold for significance. Conclusions: Fontan patients are prone to developing both portal and sinusoidal fibrosis. Liver stiffness could be influenced by HVPG, and using the conventional cut‐off values for LS overestimates and overtreats liver fibrosis in these patients.